2014
DOI: 10.1111/jre.12235
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐33 could play an important role in the pathogenesis of periodontitis

Abstract: The experimental periodontitis group exhibited increased expression of IL-33 and RANKL compared with the healthy group. Additionally, there was a positive correlation between these expressions. According to these results, IL-33 could be associated with the pathogenesis of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 43 publications
(94 reference statements)
0
38
0
1
Order By: Relevance
“…Hence, multiple tissues are included in this region, such as the alveolar bone above the line of the apex of the two tooth roots, the periodontal ligaments (PDLs) between the adjacent two roots and the gingival tissues between the two teeth. The number of inflammatory cells and osteoclasts in the DRs was counted according to the cell morphologies, as previously reported . Briefly, the DRs in each section were divided into three equidistant parts (top, middle, and bottom); then, at 400× magnification, the cell number in three randomly selected fields of each part was obtained, and the mean cell number in the DRs was then calculated .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, multiple tissues are included in this region, such as the alveolar bone above the line of the apex of the two tooth roots, the periodontal ligaments (PDLs) between the adjacent two roots and the gingival tissues between the two teeth. The number of inflammatory cells and osteoclasts in the DRs was counted according to the cell morphologies, as previously reported . Briefly, the DRs in each section were divided into three equidistant parts (top, middle, and bottom); then, at 400× magnification, the cell number in three randomly selected fields of each part was obtained, and the mean cell number in the DRs was then calculated .…”
Section: Methodsmentioning
confidence: 99%
“…The number of inflammatory cells and osteoclasts in the DRs was counted according to the cell morphologies, as previously reported. 30,31 Briefly, the DRs in each section were divided into three equidistant parts (top, middle, and bottom); then, at 400× magnification, the cell number in three randomly selected fields of each part was obtained, and the mean cell number in the DRs was then calculated. 32 For determination of the number of osteoclasts in HE-stained slides, the presence of 2 or more nuclei and the osteoclast localization (adjacent to the bone surface) were used as parameters to identify osteoclasts.…”
Section: Micro-ct Scanning and Analysismentioning
confidence: 99%
“…Recently, it has been also shown that TNF‐α induces IL‐33 expression in human gingival fibroblasts isolated from human periodontitis samples . In addition, increased expression of IL‐33 has been demonstrated in an experimental rat model of periodontitis . To better understand the role of IL‐33 in chronic apical periodontitis, we investigated the expression pattern of IL‐33 in both periapical granulomas and radicular cysts, as well as in healthy periapical tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of ligature induced-periodontitis, IL-33 expression was upregulated concomitantly to RANK-L [19]. In human, high IL-33 overexpression was recorded in the gingiva of patients affected by CP and may act as a triggering factor for the recruitment of B and T lymphocytes expressing RANK-L [20].…”
Section: Introductionmentioning
confidence: 99%